Marketing of Educational Services: A New Strategy for Customer Satisfaction (International Journal of Scientific Research and Management (IJSRM), 2013)
Students and the parents are aware that the cost of education has been on the rise irrespective of mushroom growth of educational institutions. Already there is cutthroat competition among various private educational institutions. This competition will become more aggressive if the foreign universities are allowed to open their study centres in India. Albeit quality and employability are the main concerns of responsible institutions, money minting institutions which aim high rate of return lure and divert the parents and the students through attractive ads, by bypassing customer satisfaction. However, the success of these institutions will be possible only in the short run. Under these circumstances, building customer loyalty through customer satisfaction has become a challenging one. A well designed educational marketing strategy is the need of the hour for ensuring success and survival in the market. There are some key considerations-i.e., Education should be Approachable, Applicable, Adaptable and Appraisable. These 4A’s should be the ‘mantra’ of any educational institution for ensuring success in the market. Right communication strategy at the right time can ensure easy approachability. Introduction of relevant and fresh curricula can guarantee the employability of a student. Any system that is introduced should be adaptable. Otherwise, there will be total dilution and the entire plan of the organisation will be collapsed. After adapting the scheme, it should be evaluated properly to know the results and identify the changes required for further improvement. This paper is an attempt to identify the strategy to be applied by the educational institutions in marketing their services in order to ensure their success and survival